Identification for Development : Nigeria - World Bank (World Bank, Washington, DC, 2017)
The Nigerian federal government recognized the need to create a national identity program, incorporating lessons from past attempts of Department of National Civic Registration, and following leading practices of national identity programs in other countries. With an aim to create a comprehensive identity system, Nigeria constituted "The Committee on the Harmonisation of National Identity Cards" to create a national policy and institutional framework for an identity management system in Nigeria. As per the recommendation of the Committee, and subsequent enactment of a law, the government established NIMC as the agency responsible for developing a National Identity Management System (NIMS). several government agencies issue an identity credential to residents for specific uses, but NIMC leads the identity agenda of Nigeria, and offers a "foundational identity" or an "official identity."